Measurement of complement activation via plasma soluble C5b-9 comparison with terminal complement complex staining in a series of kidney biopsies - Carolyn Wijaya; Christine Burns; Sharron Hall; Melissa Farmer; Denise Jones; Matthew Rowlandson; Peter Choi; Mark Formby; Theo de Malmanche (Karger Publishers, 2023)
Introduction: With the emergence of therapeutic complement inhibitors, there is a need to identify patients with complement-driven inflammation. C5b-9 is the terminal product of the three complement pathways, and therefore a marker of total complement activation. We present a pilot study which aims to assess whether plasma soluble C5b-9 (sC5b-9) correlates with terminal complement complex (TCC) staining in kidney tissue. The secondary aim was to assess the utility of plasma sC5b-9 as part of routine work up in kidney patients undergoing kidney biopsy. Methods: 37 patients undergoing kidney biopsy had plasma sC5b-9 and TCC staining on kidney tissue performed. Additional blood markers including creatinine, haemoglobin, CRP, Factor H, Factor I and midkine levels were also taken. These parameters were correlated with the histological diagnoses. Patients were divided into a diseased group (n=31), and a control group (n=6) consisting of transplanted kidneys with minor or no changes. Of the biopsies in the control group, 50% were performed as per protocol, and the other 50% were performed due to clinical need. Results: There was no correlation found between plasma sC5b-9 and TCC kidney staining. Elevated sC5b-9 levels were found in a heterogeneous group of patients, but were associated with higher CRP and lower haemoglobin levels. Overall, there was more TCC kidney staining in the diseased group compared with the control group, and a trend was observed of diabetic, primary membranous nephropathy and amyloidosis patients having more intense glomerular and peritubular/interstitial staining. Discussion/Conclusion: Plasma sC5b-9 as a marker of total complement activation does not correlate with TCC kidney staining. This discordance suggests that plasma sC5b-9 and TCC staining are distinct markers of disease. TCC staining reflects chronicity and tissue deposition of complement over time. Conversely, plasma sC5b-9 concentrations change rapidly and reflect systemic complement activation. Complement activation was present in a heterogeneous group of kidney disease, indicating the underlying role of complement in many disorders.